Social Forestry Policy Post the Job Creation Law Promulgation: Is This the Answer to Materialize Sustainable Forest Development? - Wilda Prihatiningtyas; Zuhda Mila Fitriana; Suparto Wijoyo; Nur Indah Apriani Tiban (Future Science, 2022)
The enactment of The Job Creation Law (JCL) affects various national regulations in Indonesia, one of which is forestry regulation. The Social Forestry Program, which was previously governed under a Ministerial Regulation, is now incorporated in the JCL. The JCL amends Indonesian National Forestry Law in its Articles 29 (a) and (b). The integration of the Social Forestry Program is asserted to have provided legal certainty and improvement towards the economy of the Forest Village Community, acknowledging their direct participation in managing the forest. Meanwhile, the alignment of the Social Forestry Program and the materialization of sustainable forest development is diminished. Thus, this paper aims to analyze which law models fit to strengthen the Social Forestry Program and Sustainable Forest Management (SFM) enforcement. This paper is an empirical research juridical research that is participatory. It includes discussions and interviews conducted with several related parties. In the collection of the legal materials, the authors use the method of inventory and documentation which are complemented by interviews and Focus Group Discussion (FGD). This study uses the statutory, conceptual as well as case approaches. This research finds that the ease of conducting investment encouraged by the JCL conflicted of various Indonesian environmental protection goals. For instance, the risk-based approach used in the environmental permit generates another loophole for both the SFM and the Sustainable Development Management (SDM) goals at any level. The discussion in this research is restricted by the national concept of the Social Forestry Program, which is merely regulated at the ministerial level, thus affecting the development of this study. Moreover, the authors pursue discussions with the affected community and relevant regional boards to redress the limited and less-updated supporting data available.